Biologically active indole and bisindole alkaloids from Leuconotis and Kopsia / Gan Chew Yan - Gan, Chew Yan (2013)

(untitled)
Two Malaysian plants viz., Leuconotis griffithii and Kopsia pauciflora, and one fungi strain (Penicillium sp. (CDA p48.3)) were investigated for their alkaloidal content and the results are summarized below (Table). A total of 107 alkaloids were isolated and characterized from these sources. Of these, 37 are new alkaloids. Leuconotis griffithii yielded a total of 24 new alkaloids, of which sixteen, viz., the tetracyclic ring-opened oxindole leucolusine (1), the strychnan alkaloids, leuconicines AG (28), the ring-C contracted rhazinilam alkaloid, nor-rhazinicine (22), the unprecedented eburnanequinoline dimer, leucophyllidine (36), the eburnanesarpagine bisindole, leuconoline (37), the aspidospermatanaspidospermatan bisindole, leucofoline (38), and the StrychnosStrychnos bisindoles, leucoridines AD (3942), are notable for incorporating novel or intriguing molecular skeletons. The stem-bark and leaf extracts of Kopsia pauciflora gave a total of 10 new alkaloids. These new alkaloids are the seco-leuconoxine alkaloid, compound 62, the eburnane alkaloids, 6364, the corynanthean oxindole alkaloids, 6971, the corynanthean pseudoindoxyl alkaloid, tetrahydroalstonine pseudoindoxyl (73), the aspidofractinine alkaloid, 11,12-dimethoxykopsinaline (77), and the andransinine alkaloids, andransinine (90) and compound 91. The culture broth extract of a Penicillium sp. (CDA p48.3) gave three new variotin derivatives, viz., compounds 101103. Among the new alkaloids, 5,21-dihydrorhazinilam N-oxide (23), leucophyllidine (36), and leucoridine A (39) showed pronounced cytotoxic effects against human KB cells (IC50 0.572.95 g/mL), while leuconodine B (10), leuconodine D (12), nor-rhazinicine (22), leuconoline (37), leucofoline (38), and leucoridines BD (4042) showed only moderate to weak activity (IC50 7.0617.90 g/mL). Leuconicines AB (23), compound 70, and andransinine iii (90) were found to be effective in circumventing MDR in vincristine-resistant KB cells (IC50 1.612.75 g/mL), while leuconicines CE (46), leuconodine E (13), and compounds 62, 64, and 91, showed only moderate to weak activity (IC50 3.8618.13 g/mL).